(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
Women’s participation in Dapha musical schooling and gathering is a recent phenomenon. Most of the Dapha Khal at Kirtipur observed exclusively male participant. Very few Dapha Khal trained and included women as hymn singers and musicians. We observed that seniors and young, males and few young females participated in a few Daphas at temples and Falchas regularly. In comparison to caste women, Newar women were considered active and dominant participants of decision-making in the family and community. The article tries to address: Why were Dapha Khal exclusively male musical institutions? How and why are females included in training and Dapha hymn singing within the limited Dapha? What are the experiences of female negotiation in Dapha Khal? Being members and residents of the Newar community, we tried to explore gender and musical relations through the integration of religions, livelihood, and historical trajectories of the musical institution. The qualitative study was carried out by employing key informant interviews, observations and archival research methods. We talked to both male and female participants when they were engaged at Dapha Khal music. We tried to explore how gender, sacred and social orders interact and negotiate in various contexts at the Newar community of Kirtipur. Through Dapha musical culture, their gendered negotiation and rupture are explained and interpreted. The historical trajectories of livelihood, gender roles, political-economic changes, education, religious and musical transformations empowered women to negate gendered narratives of Dapha music. They encouraged young girls, seniors and the Dapha community to train and involve females in Dapha musical activities. The resistance and inclusion of females in Dapha contribute not only significant changes on religious narratives but also strengthen gender and social harmony in society.